Nano microgel, preparation method thereof and application of nano microgel in repairing aged SBS (styrene-butadiene-styrene) modified asphalt
By using special nano microgels to repair aged SBS modified asphalt, the problem of poor recovery effect in the prior art is solved, and the performance recovery and environmentally friendly repair process of asphalt pavement are achieved.
Patent Information
- Application Number
- CN202510030224.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-11
AI Technical Summary
The existing waste SBS modified asphalt regeneration technology cannot effectively restore the initial road performance of asphalt pavement, and cannot form a microscopic spatial network structure, resulting in poor recovery effect.
A nanomicrogel is used, which consists of acrylic soft monomer, a crosslinking agent, a vinyl silane coupling agent, a multifunctional epoxy monomer, an initiator, a terminator and a solvent, and a nanomicrogel with a three-dimensional spatial crosslinking structure is formed by a specific preparation method and used to repair aged SBS modified asphalt.
Nanomicrogels can not only repair SBS small molecule chain segments and restore cross-linked linear structures, but also strengthen aged asphalt through its own spatial network structure and react with asphalt components to improve the various properties of asphalt, so that the regenerated SBS modified asphalt can be restored to the initial road performance, and can be repaired at room temperature, saving energy consumption and more environmentally friendly.
Smart Images

Figure SMS_1 
Figure HDA0005233930340000011 
Figure HDA0005233930340000012
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of waste asphalt regeneration, and more specifically, to a nano-microgel and a preparation method thereof and an application thereof in repairing aged SBS modified asphalt. Background Art
[0002] Asphalt pavement is widely used in highway construction due to its advantages such as smooth surface, no expansion joints, comfortable driving, low noise, easy construction and maintenance, etc. However, with the rapid development of highway construction, ordinary asphalt pavement can no longer meet the structural requirements of modern transportation and pavement. Therefore, since the 1990s, SBS modified asphalt has been gradually applied to pavement at home and abroad to improve the high temperature rutting resistance, low temperature crack resistance, water stability, fatigue resistance and other pavement properties of asphalt pavement.
[0003] Although SBS modified asphalt pavement has many excellent properties, it will also be affected by ultraviolet light, heat, oxygen and other factors during service, causing SBS modified asphalt to age, resulting in pavement damage. The pavement also needs to be repaired or rebuilt, which will inevitably produce a large amount of waste SBS modified asphalt mixture. If these waste SBS modified asphalt mixtures are directly discarded, it will not only cause a waste of resources, but also cause a heavy burden on the environment. Therefore, people began to study how to recycle waste SBS modified asphalt mixtures.
[0004] At present, the regeneration technology of waste SBS modified asphalt mixture usually uses a regeneration agent to react with aged SBS modified asphalt to improve its road performance. However, most of the existing regeneration agents only make up for the light components lost by SBS modified asphalt due to aging, or can only connect the broken SBS small molecule segments to restore the original cross-linked linear structure, and cannot form a microscopic spatial network structure. The restoration effect is still unsatisfactory and cannot meet the original road performance standards of SBS modified asphalt. Summary of the invention
[0005] In order to solve the above technical problems, the present application provides a nano-microgel and a preparation method thereof and an application thereof in repairing aged SBS modified asphalt.
[0006] In the first aspect, the present application provides a nano-microgel, which adopts the following technical solution: A nano-microgel, the raw materials used include the following components in parts by weight: 33-44 parts of acrylic soft monomer; 3-4 parts of cross-linking agent; 1-2 parts of vinyl silane coupling agent; 1-2 parts of multifunctional epoxy monomer; Initiator 0.1-0.2 parts; Terminator 0.3-0.5 parts; 40-50 parts of solvent.
[0007] Optionally, the acrylic soft monomer includes one or more of ethyl acrylate, butyl acrylate, acrylic acid, hydroxybutyl acrylate, isooctyl acrylate, methyl methacrylate, lauryl acrylate, isobornyl acrylate and vinyl acetate.
[0008] In a preferred embodiment, the acrylic soft monomer comprises butyl acrylate, acrylic acid, hydroxybutyl acrylate and methyl methacrylate in a weight ratio of (5-7):(7-10):(1-2):(20-25).
[0009] Optionally, the crosslinking agent includes one or more of trimethylolpropane trimethacrylate, acrylamide, N-(hydroxymethyl)acrylamide, diacetone acrylamide, acetoacetoxyethyl methacrylate and dimethylaminoethyl methacrylate.
[0010] In a preferred embodiment, the crosslinking agent is trimethylolpropane trimethacrylate.
[0011] Optionally, the vinyl silane coupling agent includes one or more of vinyl trichlorosilane, vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri(β-methoxyethoxy)silane, 3-aminopropyl triethoxysilane and N-(2-aminoethyl)-y-aminopropyl trimethoxysilane.
[0012] In a preferred embodiment, the vinyl silane coupling agent is 3-aminopropyltriethoxysilane.
[0013] Optionally, the multifunctional epoxy monomer includes one or more of 1,6-hexanediol diglycidyl ether, 1,4-butanediol diglycidyl ether, and glycidyl methacrylate.
[0014] In a preferred embodiment, the multifunctional epoxy monomer is glycidyl methacrylate.
[0015] Optionally, the terminator includes one or more of octadecyl acrylate, p-benzoquinone, nitrobenzene and trinitrobenzene.
[0016] In a preferred embodiment, the terminator is octadecyl acrylate.
[0017] Optionally, the solvent includes one or more of propylene glycol methyl ether, butanone, ethyl acetate, cyclohexane, n-heptane and cyclohexanone.
[0018] In a preferred embodiment, the solvent comprises propylene glycol methyl ether and butanone in a weight ratio of (0.5-1.5):1.
[0019] In a second aspect, the present application provides a method for preparing the above-mentioned nano-microgel, using the following technical solution: A method for preparing a nano-microgel, comprising the following steps: S1. Under the conditions of 70-80° C., vacuum environment and inert gas protection, adding acrylic soft monomer and multifunctional epoxy monomer to a solvent with a total amount of 65-75 wt % of the solvent and mixing them uniformly to obtain a mixture A; and mixing a solvent with a total amount of 5-15 wt % of the solvent and an initiator uniformly to obtain a mixture B; S2. Add mixture B dropwise to mixture A at a temperature of 70-80°C, a rotation speed of 300-400 r / min, a vacuum environment and inert gas protection. After the addition is completed, react at a temperature of 60-80°C for 0.5-1.5h; S3, adding the mixture of the remaining solvent, the vinyl silane coupling agent and the terminator dropwise to the reactant obtained in step S2, and reacting at a temperature of 60-80° C. for 0.5-1.5 h after the addition is completed; S4, adding the cross-linking agent dropwise to the reactant obtained in step S3, and reacting at a temperature of 75-85° C. for 1.5-2.5 hours after the addition is completed; S5. After the reaction is completed, the temperature is raised to the boiling point of the solvent to evaporate the solvent, and the nano-microgel is obtained after vacuum drying.
[0020] Through the above technical scheme, the present application firstly allows acrylic soft monomers to undergo polymerization reaction under the action of an initiator to form a main chain, and at the same time, a polymerization reaction occurs between the acrylic soft monomers and the multifunctional epoxy monomers, and the synthesized nano microgels are made to have epoxy groups by using the multifunctional epoxy monomers. Then, a vinyl silane coupling agent is added to control the crosslinking speed and the degree of crosslinking, and the synthesized nano microgels have amino groups, carboxyl groups and the like; at the same time, a terminator is added to control the length of the main chain. When the terminator is polymerized on the molecular chain, it occupies a large space, hindering the approach of other active monomers, and the main chain polymerization will be stopped, thereby achieving the purpose of controlling the size of the nano microgel. After that, a crosslinking agent is added to form a spatial network structure, and finally a nano-sized reactive microgel with a diameter of 30-50nm and a three-dimensional spatial crosslinking structure is obtained.
[0021] The nano-microgel of the present application is used to repair aged SBS modified asphalt. On the one hand, the microstructure of the nano-microgel itself can replace the macroscopic network in the aged SBS modified asphalt, that is, the structural characteristics of the nano-microgel itself and the interaction of polar bonds in the structure can be used to achieve a reinforcing effect, thereby improving the strength of the entire binder; on the other hand, it can react with asphalt components to improve the various properties of asphalt, thereby achieving the effect of enhancing the temperature stability, durability and construction performance of aged SBS modified asphalt; on the third hand, the functional groups on the nano-microgel, such as epoxy, amino, carboxyl, etc., are used to react with SBS small molecule segments to achieve the purpose of repairing SBS broken segments; ultimately, the regenerated SBS modified asphalt can be restored to its initial road performance. In addition, the polar or active groups on the surface of the nano-microgel will migrate to the surface of the regenerated SBS modified asphalt, increasing the adhesion between the interface of new and old aggregates. When the addition amount or the modification effect is equivalent, the viscosity of the SBS modified asphalt regenerated by the nano-microgel of the present application is lower, which is more conducive to processing and transportation, and is convenient for construction. It can also improve the compaction of the road surface, thereby enhancing the performance and durability of the road surface.
[0022] In a third aspect, the present application provides an application of the above-mentioned nano-microgel in repairing aged SBS modified asphalt, using the following technical solution: A nano-microgel is used in repairing aged SBS modified asphalt. The nano-microgel is mixed with an asphalt regeneration agent and aged SBS modified asphalt at a temperature of 140-160°C and a rotation speed of 200-400 rpm for 20-30 minutes. The amount of the nano-microgel added is 2-4wt% of the total amount of the aged SBS modified asphalt, and the amount of the asphalt regeneration agent added is 0.4-0.6wt% of the total amount of the aged SBS modified asphalt.
[0023] A nano-microgel is used in repairing aged SBS modified asphalt. The nano-microgel is mixed with a bio-based diluent and aged SBS modified asphalt at room temperature and a rotation speed of 200-400 rpm for 20-30 minutes. The amount of the nano-microgel added is 2-4wt% of the total amount of the aged SBS modified asphalt, and the amount of the bio-based diluent added is 0.2-0.4wt% of the total amount of the aged SBS modified asphalt.
[0024] Through the above technical scheme, the nano-microgel of the present application can not only repair aged SBS modified asphalt by conventional hot mixing method, but also repair aged SBS modified asphalt at room temperature, so that the regenerated SBS modified asphalt can achieve the initial road performance, save energy consumption, and be more environmentally friendly.
[0025] The asphalt regeneration agent of the present application is a commonly used asphalt regeneration agent in the art, such as aromatic oil, extracted oil, etc., wherein the content of aromatic components in the extracted oil is greater than 65wt%.
[0026] The bio-based diluent of the present application is prepared by mixing linseed oil, soybean oil, refined waste oil and limonene, and its effect is similar to that of asphalt regeneration agent, which is mainly used to soften aged SBS modified asphalt and make up for the missing light components in the aged SBS modified asphalt.
[0027] In summary, this application has the following beneficial technical effects: 1. The nano-microgel of the present application can not only link the broken SBS small molecule segments to restore the original cross-linked linear structure, but also use its own spatial network cross-linked structure to reinforce the aged SBS modified asphalt. At the same time, it can react with asphalt to improve the various properties of asphalt. It has a strong recovery effect on the aged SBS modified asphalt. The repaired SBS modified asphalt can restore the original road performance standards; 2. The preparation method of the present application obtains a nano-sized reactive microgel with a three-dimensional spatial cross-linked structure through molecular design, and its diameter is detected to be 30-50nm. The steps are simple, easy to operate, and suitable for large-scale industrial use; 3. The nano-microgel of the present application can not only repair aged SBS modified asphalt by conventional hot-mixing method, but also repair aged SBS modified asphalt at room temperature. The regenerated SBS modified asphalt can achieve the initial road performance, save energy consumption, and be more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a diagram showing the size measurement results of the nano-microgel prepared in Example 3 of the present application; Figure 2 It is a schematic diagram of using the nano-microgel of the present application to repair an aged SBS modified asphalt binder matrix; Figure 3 This is the infrared spectrum of the regenerated SBS modified asphalt after the aged SBS modified asphalt is repaired by the nano-microgel of the present application. DETAILED DESCRIPTION
[0029] Unless otherwise specified, the raw materials used in this application are all commercially available products.
[0030] In some specific embodiments of the nano-microgel, the acrylic soft monomer includes one or more of ethyl acrylate, butyl acrylate, acrylic acid, hydroxybutyl acrylate, isooctyl acrylate, methyl methacrylate, lauryl acrylate, isobornyl acrylate and vinyl acetate.
[0031] In some preferred embodiments, the acrylic soft monomer includes butyl acrylate, acrylic acid, hydroxybutyl acrylate and methyl methacrylate in a weight ratio of (5-7):(7-10):(1-2):(20-25).
[0032] In some specific embodiments of the nano-microgel, the crosslinking agent includes one or more of trimethylolpropane trimethacrylate, acrylamide (AAM), N-(hydroxymethyl)acrylamide (NMA), diacetone acrylamide (DAAM), acetoacetoxyethyl methacrylate (AAEM) and dimethylaminoethyl methacrylate (DMAEMA).
[0033] In some preferred embodiments, the crosslinking agent is trimethylolpropane trimethacrylate.
[0034] In some specific embodiments of the nano-microgel, the vinyl silane coupling agent includes one or more of vinyl trichlorosilane, vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri(β-methoxyethoxy)silane, 3-aminopropyl triethoxysilane and N-(2-aminoethyl)-y-aminopropyl trimethoxysilane.
[0035] In some preferred embodiments, the vinyl silane coupling agent is 3-aminopropyltriethoxysilane.
[0036] In some specific embodiments of the nano-microgel, the multifunctional epoxy monomer includes one or more of 1,6-hexanediol diglycidyl ether, 1,4-butanediol diglycidyl ether, and glycidyl methacrylate.
[0037] In some preferred embodiments, the multifunctional epoxy monomer is glycidyl methacrylate.
[0038] In some embodiments of the nano-microgel, the initiator includes one or more of azobisisobutyronitrile, benzoyl peroxide and di-tert-butyl peroxide.
[0039] In some preferred embodiments, the initiator is azobisisobutyronitrile.
[0040] In some embodiments of the nano-microgel, the terminator includes one or more of octadecyl acrylate, p-benzoquinone, nitrobenzene and trinitrobenzene.
[0041] In some preferred embodiments, the terminator is octadecyl acrylate, CAS No. 4813-57-4.
[0042] In some embodiments of the nano-microgel, the solvent includes one or more of propylene glycol methyl ether, butanone, ethyl acetate, cyclohexane, n-heptane and cyclohexanone.
[0043] In some preferred embodiments, the solvent comprises propylene glycol methyl ether and butanone in a weight ratio of (0.5-1.5):1.
[0044] In some specific embodiments of the nano-microgel, the above raw materials are used, and the following steps are followed: S1, under the conditions of a temperature of 70-80° C., a vacuum environment and protection of inert gas, an acrylic soft monomer and a multifunctional epoxy monomer are added to a solvent with a total amount of 65-75wt% of the solvent and mixed evenly to obtain a mixture A; a solvent with a total amount of 5-15wt% of the solvent and an initiator are mixed evenly to obtain a mixture B; S2, under the conditions of a temperature of 70-80° C., a rotation speed of 300-400r / min, a vacuum environment and protection of inert gas, the mixture B is added dropwise to the mixture; S3, adding the mixture of the remaining solvent, vinyl silane coupling agent and terminator to the reactant obtained in step S2, and reacting at 60-80°C for 0.5-1.5h after the addition is completed; S4, adding the cross-linking agent to the reactant obtained in step S3, and reacting at 75-85°C for 1.5-2.5h after the addition is completed; S5, after the reaction is completed, raising the temperature to the boiling point of the solvent to evaporate the solvent, and obtaining a nano-microgel with a diameter of 30-50nm after vacuum drying.
[0045] The nano-microgel prepared above was used to repair aged SBS modified asphalt in the following two ways, and the regenerated SBS modified asphalt could reach the original road performance level.
[0046] The first method is to mix the above-prepared nano-microgel with asphalt regeneration agent and aged SBS modified asphalt at a temperature of 140-160°C and a rotation speed of 200-400rpm for 20-30min, wherein the amount of the nano-microgel added is 2-4wt% of the total amount of the aged SBS modified asphalt, and the amount of the asphalt regeneration agent added is 0.4-0.6wt% of the total amount of the aged SBS modified asphalt.
[0047] The asphalt regeneration agent is a commonly used asphalt regeneration agent in the art, such as aromatic oil, extracted oil, etc., and the content of aromatic components in the extracted oil is greater than 65wt%. In the specific implementation of the present application, aromatic oil is used as an example for description.
[0048] The second method: at room temperature and a rotation speed of 200-400 rpm, the above-prepared nano-microgel is mixed with a bio-based diluent and aged SBS modified asphalt for 20-30 minutes, wherein the amount of the nano-microgel added is 2-4wt% of the total amount of the aged SBS modified asphalt, and the amount of the bio-based diluent added is 0.2-0.4wt% of the total amount of the aged SBS modified asphalt.
[0049] Among them, the bio-based diluent is made by mixing linseed oil, soybean oil, refined waste oil and limonene.
[0050] In some preferred embodiments, the weight ratio of linseed oil, soybean oil, refined waste oil and limonene is 30:20:20:30.
[0051] In combination with the above content, the applicant further uses the following application examples 1-5 and comparative application examples 1-3 to further demonstrate the repair effect of the nano-microgel of the present application on aged SBS modified asphalt. Since the current traditional regeneration agent can only have a good repair effect on aged SBS modified asphalt under hot mixing conditions, this application uses the first method as an example to compare and verify the repair effect of the nano-microgel.
[0052] In order to more conveniently evaluate the repair effect of the nano-microgel of the present application on aged SBS modified asphalt, the present application simulates the aging of SBS modified asphalt during long-term use of the pavement by using a rotating film oven with a delay of 300 minutes to obtain aged SBS modified asphalt. The specific preparation method is as follows: The softening point of the unaged SBS modified asphalt is 62.5℃, the elongation at 5℃ is 40.5cm, the needle penetration at 25℃ is 48.3dmm, and the viscosity at 135℃ is 2560mPa·s. It is aged in a rotary film oven at 163℃ for 300min and then exposed to ultraviolet light at an intensity of 1300μW / cm -1 The asphalt was irradiated in an ultraviolet aging box at 40°C (the wavelength of ultraviolet light was 365nm) for 14 days to obtain aged SBS modified asphalt. The softening point of the aged SBS modified asphalt was 69.8°C, the elongation at 5°C was 6.6cm, the penetration at 25°C was 30.8dmm, and the viscosity at 135°C was 4040mPa·s.
[0053] Example 1 A method for preparing a nano-microgel comprises the following steps: S1, 2600g solvent (propylene glycol methyl ether 867g, butanone 1733g) was added to a reactor, evacuated at room temperature and nitrogen was introduced, and the temperature was raised to 70°C under the protection of nitrogen after 5 cycles, 500g butyl acrylate, 700g acrylic acid, 100g hydroxybutyl acrylate, 2000g methyl methacrylate and 200g glycidyl methacrylate were added and mixed to obtain a mixture A; 200g solvent (propylene glycol methyl ether 67g, butanone 133g) and 10g azobisisobutyronitrile were mixed to obtain a mixture B; S2. Add mixture B to mixture A at a flow rate of 8 mL / min under the conditions of 70°C, 300 r / min, vacuum environment and inert gas protection. After the addition is completed, react at 60°C for 0.5 h. S3, adding a mixture of 1200 g of solvent (67 g of propylene glycol methyl ether and 133 g of butanone), 100 g of 3-aminopropyltriethoxysilane and 50 g of octadecyl acrylate dropwise to the reactant obtained in step S2, and reacting at a temperature of 60° C. for 0.5 h after the addition is completed; S4, adding 400 g of trimethylolpropane trimethacrylate dropwise to the reactant obtained in step S3, and reacting at a temperature of 75° C. for 1.5 h after the addition is completed; S5. After the reaction is completed, the temperature is raised to the boiling point of the solvent to evaporate the solvent, and the nano-microgel is obtained after vacuum drying.
[0054] Example 2 A method for preparing a nano-microgel comprises the following steps: S1, 2924g solvent (propylene glycol methyl ether 1300g, butanone 1624g) was added to the reactor, evacuated at room temperature and nitrogen was introduced, and the temperature was raised to 72°C under the protection of nitrogen after 6 cycles, 550g butyl acrylate, 750g acrylic acid, 120g hydroxybutyl acrylate, 2080g methyl methacrylate and 170g glycidyl methacrylate were added and mixed to obtain a mixture A; 344g solvent (propylene glycol methyl ether 153g, butanone 191g) and 12g azobisisobutyronitrile were mixed to obtain a mixture B; S2. Add mixture B to mixture A at a flow rate of 8 mL / min under the conditions of a temperature of 72°C, a rotation speed of 330 r / min, a vacuum environment and inert gas protection. After the addition is completed, react at a temperature of 65°C for 0.8 h. S3, adding a mixture of 1032 g of solvent (459 g of propylene glycol methyl ether and 573 g of butanone), 120 g of 3-aminopropyltriethoxysilane and 46 g of octadecyl acrylate dropwise to the reactant obtained in step S2, and reacting at a temperature of 65° C. for 0.8 h after the addition is completed; S4, adding 380 g of trimethylolpropane trimethacrylate dropwise to the reactant obtained in step S3, and reacting at a temperature of 77° C. for 1.8 h after the addition is completed; S5. After the reaction is completed, the temperature is raised to the boiling point of the solvent to evaporate the solvent, and the nano-microgel is obtained after vacuum drying.
[0055] Example 3 A method for preparing a nano-microgel comprises the following steps: S1, 3150g solvent (propylene glycol methyl ether 1575g, butanone 1575g) was added to the reactor, evacuated at room temperature and nitrogen was introduced, and the temperature was raised to 75°C under the protection of nitrogen after 8 cycles, 600g butyl acrylate, 850g acrylic acid, 150g hydroxybutyl acrylate, 2250g methyl methacrylate and 150g glycidyl methacrylate were added and mixed to obtain a mixture A; 450g solvent (propylene glycol methyl ether 225g, butanone 225g) and 15g azobisisobutyronitrile were mixed to obtain a mixture B; S2. Add mixture B to mixture A at a flow rate of 8 mL / min under the conditions of a temperature of 75°C, a rotation speed of 350 r / min, a vacuum environment and inert gas protection. After the addition is completed, react at a temperature of 70°C for 1 h. S3, adding a mixture of 900 g of solvent (450 g of propylene glycol methyl ether, 450 g of butanone), 150 g of 3-aminopropyltriethoxysilane and 40 g of octadecyl acrylate dropwise to the reactant obtained in step S2, and reacting at a temperature of 70° C. for 1 h after the addition is completed; S4, adding 350 g of trimethylolpropane trimethacrylate dropwise to the reactant obtained in step S3, and reacting at a temperature of 80° C. for 2 h after the addition is completed; S5. After the reaction is completed, the temperature is raised to the boiling point of the solvent to evaporate the solvent, and the nano-microgel is obtained after vacuum drying.
[0056] Example 4 A method for preparing a nano-microgel comprises the following steps: S1, 3456g solvent (propylene glycol methyl ether 1885g, butanone 1571g) was added to the reactor, evacuated at room temperature and nitrogen was introduced, and the temperature was raised to 77°C under the protection of nitrogen after 10 cycles, 650g butyl acrylate, 900g acrylic acid, 180g hydroxybutyl acrylate, 2370g methyl methacrylate and 130g glycidyl methacrylate were added and mixed to obtain a mixture A; 624g solvent (propylene glycol methyl ether 340g, butanone 284g) and 17g azobisisobutyronitrile were mixed to obtain a mixture B; S2. Add mixture B to mixture A at a flow rate of 8 mL / min under the conditions of a temperature of 78°C, a rotation speed of 370 r / min, a vacuum environment and inert gas protection. After the addition is completed, react at a temperature of 75°C for 1.3 h; S3, adding a mixture of 720 g of solvent (393 g of propylene glycol methyl ether and 327 g of butanone), 180 g of 3-aminopropyltriethoxysilane and 34 g of octadecyl acrylate dropwise to the reactant obtained in step S2, and reacting at a temperature of 75° C. for 1.3 h after the addition was completed; S4, adding 320 g of trimethylolpropane trimethacrylate dropwise to the reactant obtained in step S3, and reacting at a temperature of 82° C. for 2.2 h after the addition is completed; S5. After the reaction is completed, the temperature is raised to the boiling point of the solvent to evaporate the solvent, and the nano-microgel is obtained after vacuum drying.
[0057] Example 5 A method for preparing a nano-microgel comprises the following steps: S1, 3750g solvent (propylene glycol methyl ether 2250g, butanone 1500g) was added to the reactor, evacuated at room temperature and nitrogen was introduced, and the temperature was raised to 80°C under the protection of nitrogen after 10 cycles, 700g butyl acrylate, 1000g acrylic acid, 200g hydroxybutyl acrylate, 2500g methyl methacrylate and 100g glycidyl methacrylate were added and mixed to obtain a mixture A; 750g solvent (propylene glycol methyl ether 450g, butanone 300g) and 20g azobisisobutyronitrile were mixed to obtain a mixture B; S2. Add mixture B to mixture A at a flow rate of 8 mL / min under the conditions of 80°C, 400 r / min, vacuum environment and inert gas protection. After the addition is completed, react at 80°C for 1.5 h. S3, adding a mixture of 500 g of solvent (300 g of propylene glycol methyl ether, 200 g of butanone), 200 g of 3-aminopropyltriethoxysilane and 30 g of octadecyl acrylate dropwise to the reactant obtained in step S2, and reacting at a temperature of 80° C. for 1.5 h after the addition is completed; S4, adding 300 g of trimethylolpropane trimethacrylate dropwise to the reactant obtained in step S3, and reacting at a temperature of 85° C. for 2.5 h after the addition is completed; S5. After the reaction is completed, the temperature is raised to the boiling point of the solvent to evaporate the solvent, and the nano-microgel is obtained after vacuum drying.
[0058] Application Examples 1-5 An application of nano-microgel in repairing aged SBS modified asphalt comprises the following steps: At a temperature of 150° C. and a rotation speed of 300 rpm, 3 kg of the nano-microgel prepared in the above Examples 1-5, 0.5 kg of aromatic oil and 100 kg of aged SBS modified asphalt were mixed and stirred for 25 minutes.
[0059] Comparative application example 1 The difference from Application Example 3 is that the nano-microgel prepared in Example 3 is replaced by 1,6-hexanediol diglycidyl ether, and the rest is the same as Example 3.
[0060] Comparative Application Example 2 The difference from Application Example 3 is that the nano-microgel prepared in Example 3 is replaced by a mixture of 4,4-diphenylmethane diisocyanate and 1,4-butanediol diglycidyl ether, wherein the weight ratio of 4,4-diphenylmethane diisocyanate to 1,4-butanediol diglycidyl ether is 1:1, and the rest is the same as Example 3.
[0061] Comparative Application Example 3 The difference from Application Example 3 is that the nano-microgel prepared in Example 3 is replaced by a mixture of 1,6-hexanediol diglycidyl ether, linear SBS resin and terpene resin, wherein the weight ratio of 1,6-hexanediol diglycidyl ether, linear SBS resin and terpene resin is 15:8:5, and the rest is the same as Example 3.
[0062] Performance Testing 1. The size of the nano-microgels prepared in the above-mentioned Examples 1-5 was measured. The measurement results show that the diameters of the nano-microgels prepared in Examples 1-5 of the present application are all within the range of 30-50 nm. Taking Example 3 as an example, Figure 1 As shown, the diameter of the prepared nano-microgel is 32 nm, and the measurement results of other embodiments are not described in detail with reference to the drawings.
[0063] 2. With reference to JTJT20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering", the physical properties of the SBS modified asphalt repaired in the above application examples 1-5 and comparative application examples 1-3 were tested, and the results are shown in Table 1.
[0064] Table 1 Performance test results From the data in Table 1, it can be seen that the softening point of the regenerated SBS modified asphalt obtained after the nano-microgel repair of the present application is 68.7-71.2°C, the elongation at 5°C is 35.6-38.7cm, the needle penetration at 25°C is 48.2-48.7dmm, and the viscosity at 135°C is 1640-1840mPa·s. Figure 2-3 It can be explained that the addition of the nano-microgel of the present application can significantly improve the various properties of aged SBS modified asphalt, repair the SBS small molecule segments, re-form polybutadiene segments and polystyrene segments, and use the microstructure to replace the macrostructure in the aged SBS modified asphalt, thereby enhancing the strength of the entire binder, thereby improving the various road performance of the aged SBS modified asphalt, so that it can be restored to the original level after regeneration.
[0065] The difference between Comparative Application Examples 1-3 and Application Example 3 is that the existing regeneration agent is used to repair the aged SBS modified asphalt. As can be seen from Table 1, the repair effect of Comparative Application Examples 1-3 on the aged SBS modified asphalt is worse than that of Application Example 3, and the regenerated SBS modified asphalt cannot be restored to the original level.
[0066] In order to prove again that the nano-microgel of the present application can repair aged SBS modified asphalt at room temperature, the applicant mixed 3kg of the nano-microgel prepared in Example 3 with 0.3kg of bio-based diluent (the weight ratio of linseed oil, soybean oil, refined waste oil and limonene is 30:20:20:30) and 100kg of aged SBS modified asphalt for 25 minutes at room temperature and a rotation speed of 300rpm. After testing, the softening point of the regenerated SBS modified asphalt obtained after the repair was 71.0℃, the elongation at 5℃ was 38.0cm, the needle penetration at 25℃ was 48.7dmm, and the viscosity at 135℃ was 1640mPa·s. It can be seen from the test results that the nano-microgel of the present application can also play a good repair effect on aged SBS modified asphalt at room temperature.
[0067] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A nano-microgel, characterized in that: The raw materials used include the following components in parts by weight: 33-44 parts of acrylic soft monomer; 3-4 parts of cross-linking agent; 1-2 parts of vinyl silane coupling agent; 1-2 parts of multifunctional epoxy monomer; Initiator 0.1-0.2 parts; Terminator 0.3-0.5 parts; 40-50 parts of solvent.
2. A nano-microgel according to claim 1, characterized in that: The acrylic soft monomer includes one or more of ethyl acrylate, butyl acrylate, acrylic acid, hydroxybutyl acrylate, isooctyl acrylate, methyl methacrylate, lauryl acrylate, isobornyl acrylate and vinyl acetate.
3. A nano-microgel according to claim 2, characterized in that: The acrylic soft monomer comprises butyl acrylate, acrylic acid, hydroxybutyl acrylate and methyl methacrylate in a weight ratio of (5-7):(7-10):(1-2):(20-25).
4. A nano-microgel according to claim 1, characterized in that: The crosslinking agent includes one or more of trimethylolpropane trimethacrylate, acrylamide, N-(hydroxymethyl)acrylamide, diacetone acrylamide, acetoacetoxyethyl methacrylate and dimethylaminoethyl methacrylate.
5. A nano-microgel according to claim 1, characterized in that: The multifunctional epoxy monomer includes one or more of 1,6-hexanediol diglycidyl ether, 1,4-butanediol diglycidyl ether and glycidyl methacrylate.
6. A nano-microgel according to claim 1, characterized in that: The terminator includes one or more of octadecyl acrylate, p-benzoquinone, nitrobenzene and trinitrobenzene.
7. The nano-microgel according to claim 1, characterized in that: The solvent includes one or more of propylene glycol methyl ether, butanone, ethyl acetate, cyclohexane, n-heptane and cyclohexanone.
8. A method for preparing the nano-microgel according to claim 1, characterized in that: The following steps are involved: S1. Under the conditions of a temperature of 70-80° C., a vacuum environment and protection of an inert gas, an acrylic soft monomer and a multifunctional epoxy monomer are added to a solvent with a total amount of 65-75 wt % of the solvent, and mixed uniformly to obtain a mixture A; a solvent with a total amount of 5-15 wt % of the solvent and an initiator are mixed uniformly to obtain a mixture B; S2. Add mixture B dropwise to mixture A at a temperature of 70-80°C, a rotation speed of 300-400 r / min, a vacuum environment and inert gas protection. After the addition is completed, react at a temperature of 60-80°C for 0.5-1.5h; S3, adding the mixture of the remaining solvent, the vinyl silane coupling agent and the terminator dropwise to the reactant obtained in step S2, and reacting at a temperature of 60-80° C. for 0.5-1.5 h after the addition is completed; S4, adding the cross-linking agent dropwise to the reactant obtained in step S3, and reacting at a temperature of 75-85° C. for 1.5-2.5 hours after the addition is completed; S5. After the reaction is completed, the temperature is raised to the boiling point of the solvent to evaporate the solvent, and the nano-microgel is obtained after vacuum drying.
9. Use of the nano-microgel according to claim 1 in repairing aged SBS modified asphalt, characterized in that: Under the conditions of temperature of 140-160° C. and rotation speed of 200-400 rpm, the nano-microgel is mixed with asphalt regeneration agent and aged SBS modified asphalt for 20-30 min, the amount of nano-microgel added is 2-4wt% of the total amount of aged SBS modified asphalt, and the amount of asphalt regeneration agent added is 0.4-0.6wt% of the total amount of aged SBS modified asphalt.
10. Use of the nano-microgel according to claim 1 in repairing aged SBS modified asphalt, characterized in that: Under the condition of room temperature and rotation speed of 200-400rpm, the nano-microgel is mixed with the bio-based diluent and aged SBS modified asphalt for 20-30min, the amount of the nano-microgel added is 2-4wt% of the total amount of the aged SBS modified asphalt, and the amount of the bio-based diluent added is 0.2-0.4wt% of the total amount of the aged SBS modified asphalt.
Citation Information
Cited By
A deodorized asphalt and a method for preparing the same
CN122647922A